STRATEGI PEMERINTAH INDONESIA MENGATASI MASALAH EKONOMI PADA MASA REFORMASI (1999 – 2004) - Fachrunnisa, Layna Kamilah; Armiyati, M.Pd, Laely; Jayusman, Iyus (Universitas Indraprasta PGRI, 2023)
The 1997 economic crisis was a miserable history for the Indonesian. The New Order government, which was unable to handle the storm of crises, made people's lives even more miserable. The economic reforms carried out by the post-New Order government were expected to overcome the crisis. This study aims to explore the various strategies adopted by the government at the beginning of the reform to deal with the crisis. The government in question is from 1999 to 2004. The research method uses the historical method with 4 steps, namely heuristics, verification, interpretation, and historiography. The years 2001 and 2002 recorded the highest inflation rates, the weakening of the rupiah exchange rate against the US dollar, and the highest annual interest rates. The strategy undertaken to deal with the economic crisis included carrying out Monetary Policy (controlling the money supply and raising SBI interest rates), bank liquidation, forming the National Economic Council, financial restructuring, and increasing investment. These various strategies have had a positive impact on reducing the rate of inflation and increasing the rate of economic growth.